Efektivitas Ekstrak Tepung Testis Sapi dalam Alih Kelamin Ikan Nila, Oreochromis niloticus L. Melalui Teknik Perendaman (The Effectiveness of BTME (Bull Testes Meal Extract) in Sex-Reversal of Tilapia through Immersion Technique) - Andri Iskandar; M. Zairin Junior; Harton Arfah (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2014)
Synthetic steroids are commonly used to sex-reverse tilapia to produce male tilapia commercially, but gradually feared a negative impact on food security and environmental sustainability. The use of new natural compound is a potential alternative to be explored, one of which is bull testes meal extract (BTME). This study aimed to evaluate the effectiveness of BTME immersion and optimal concentrations for sex-reverse tilapia to produce monosex male tilapia, and its influence on survival and growth of fish. The study consisted of 5 treatments with 3 replications: immersion treatment with BTME concentration of 1 ml l-1 (A), 3 ml l-1 (B), 5 ml l-1 (C), immersion treatment in 17α-methyltestosterone of 500 µg l-1 (K+) and without hormone immersion treatment (K-). Hormone immersion was performed on tilapia larvae aged 4 and 7 days after hatching.The fish were then maintained for 60 days. The parameters observed were: the percentage of male tilapia and intersex tilapia, survival rates, and growth rate of fish. BTME immersion for sex-reverse the tilapia larvae have significant effect on masculinization of tilapia. The highest percentage of male fish was obtained on treatment C (85.56%) and was not significantly different from K (+) (81.11 %). Immersion of tilapia in BTME or 17α-MT did not affect the survival and growth of tilapia fish.Keywords: sex reversal, bull testes meal extract (BTME), tilapia